Entrepreneurship Skills Acquisition and the Benefits amongst the Undergraduate Students in Nigeria - Undiyaundeye, Florence A.; Ekpungu Anselm Otu (European Journal of Social Science Education and Research, 2022)
There is this colonial mentality among the first generation graduates in Nigeria where there has been a craze for white collar office work alone. In recent times, the Nigeria graduates have faced a lot of frustrations from lack of achieving the white collar job so to speak. This paper is advocating the adoption of re-positioning the economic development and entrepreneurial drive for job creation, wealth creation and global competitiveness of Nigeria youths and graduates. The basic truce of this paper is to enhance a match between theory and practice as facilitated by research and development centers in the Nigerian universities to serve as a technology laboratory and incubate entrepreneurship skills. The entrepreneurship education as a compulsory course in some Nigerian university system is actually viewed as a means to empower the youths through entrepreneurship education. The paper critically looked at the role of entrepreneurship education. The purpose is to equip the individual and create the mindset to undertake the risk of venturing into applying the knowledge and skills gotten from school. Other issues like the provision of individuals with enough training to enable creativity and innovation relevant to skill acquisition to encourage self-employment and self-reliant were x-rayed. Some techniques like industrial training exercise, workshop and seminar, excursion as a vehicle in the youth empowerment and eradication of poverty and extreme hardship were mentioned. Challenges like inadequate funding, lack of training personnel and men availability of equipment were identified as issues facing entrepreneurship education. Recommendations like entrepreneurial base curriculum at all levels of education, provision of enabling environment for entrepreneurial development required for economic advancement and youth empowerment should be the key focus in Nigeria for youths and graduates from various tertiary schools as applicable.
Keywords: Skill acquisition, poverty eradication, youth empowerment, entrepreneurship education and graduate job challenges.